2022
DOI: 10.3390/ma15041414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ageing on Self-Healing Properties of Asphalt Concrete Containing Calcium Alginate/Attapulgite Composite Capsules

Abstract: Calcium alginate capsules within asphalt concrete can gradually release interior asphalt rejuvenator under cyclic loading to repair micro cracks and rejuvenate aged asphalt in-situ. However, asphalt pavement will become aged due to environmental and traffic factors during the service period. In view of this, this paper investigated the effect of ageing on the healing properties of asphalt concrete containing calcium alginate/attapulgite composite capsules under cyclic loading. The capsules were fabricated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The improvement in the level of healing was attributed to the collective action of more of the rejuvenator being released and an enhanced healing temperature. In the previous literature [ 22 , 23 , 27 , 29 , 33 , 46 , 47 ], when the test temperature was 20 °C, the asphalt concrete with the calcium alginate capsules all obtained higher healing ratios than plain asphalt concrete (without capsules).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The improvement in the level of healing was attributed to the collective action of more of the rejuvenator being released and an enhanced healing temperature. In the previous literature [ 22 , 23 , 27 , 29 , 33 , 46 , 47 ], when the test temperature was 20 °C, the asphalt concrete with the calcium alginate capsules all obtained higher healing ratios than plain asphalt concrete (without capsules).…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, the Ca alginate capsules must withstand the mechanical action created in the production period of the asphalt concrete. Practice has shown that the mechanical strength of the capsules used for bituminous mixtures must be greater than 10 N [ 33 , 34 ]. Figure 8 presents the compressive strength of the capsules after specific temperature treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of [ 40 ] present SH in microcapsule asphalt; [ 41 ] presents SH in asphalt due to the microwave heating of the pavement. The durability and aging of self-healed asphalt concrete is discussed in [ 42 ], and the performance of SH in porous asphalt is presented in [ 43 ]. Modeling SH materials is another group of articles that could be distinguished.…”
Section: Introductionmentioning
confidence: 99%